PENGARUH CORPORATE GOVERNANCE, CASH FLOW, DAN PROFIT TERHADAP FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Novelina Caesar Ramadhanti; Subagyo - - (Universitas Trilogi, 2022)
This study aims to provide empirical evidence on the effect of corporate governance, cash flow and profit on financial distress conditions in manufacturing companies in Indonesia listed on the Indonesia Stock Exchange (IDX). This research is expected to be useful as a reference for similar studies and to provide information related to financial distress conditions. The dependent variable in this study is financial distress which is measured using the Altman Z-Score model. The independent variables in this study are institutional ownership, managerial ownership, the proportion of independent commissioners, the number of boards of directors, the audit committee size, cash flow and profit. The population of this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling technique in this study used purposive sampling and data analysis techniques, namely logistic regression analysis. The results of this study indicate that institutional ownership, cash flow and profit have a significant negative effect on financial distress, then the number of boards directors and the size of the audit committee size have a significant positive effect on financial distress. Meanwhile, managerial ownership and the proportion of independent commissioners has no significant effect on financial distress conditions.